Mobile app control of Unmanned Aerial Vehicle - Adhimoolam, Anusha (2015)
Mobile phones permeate in all aspects of our lives, which increased the popularity and importance of mobile phone applications. Smartphones are constantly being upgraded not only in hardware but also in the software which incur the growth of mobile phone applications which are developed to be compatible with different operating systems. Similarly, Unmanned Aerial Vehicles (UAVs) are also gaining traction as they get more affordable with higher quality. The methodologies of the software and hardware components to build a quad-copter are easily available online; software coding is an open source for some flight controller boards which gives the developers the opportunities to add on extra features. This report seeks to provide a summary of the Final Year Project (FYP). Incorporating the aforementioned, this FYP is a continuation of a project kickstarted by Nanyang Technological University (NTU) Project Officer, Nay Aung Kyaw, who has designed an Android Application to control a quad-copter via Bluetooth using an Android phone. In this project, the application has been fine-tuned for better control of the quad-copter in Gyro mode, and User Interface has also been redesigned. In addition, the final application program and its new features, which include but not limited to voice control are covered in this report. Finally future developments and recommendations are also considered in this report.